2022
DOI: 10.1101/2022.06.21.496945
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An α-π transition in S6 shapes the conformational cycle of the bacterial sodium channel NavAb

Abstract: Voltage gated sodium channels play an important role in electrical signaling in excitable cells. In response to changes in membrane potential, they cycle between nonconducting and conducting conformations. With recent advances in structural biology, structures of sodium channels have been captured in several distinct conformations, thought to represent different functional states. However, it has been difficult to capture the intrinsically transient open state. We recently showed that a proposed open state of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 77 publications
(150 reference statements)
0
2
0
Order By: Relevance
“…11 The water density profile along the pore axis shows that the pores are continuously hydrated. Although the water density near the activation gate drops to a value below that of bulk water density (Figures 2B and S1B), it is substantially higher than that in models of the open state of bacterial channels obtained experimentally, 23,24,29 leading us to hypothesize that the presence of π-helices correlates with an increased water density. Indeed, the experimentally resolved open-state model of Nav1.5 featured two π-helixes in DI-S6 and DIII-S6.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…11 The water density profile along the pore axis shows that the pores are continuously hydrated. Although the water density near the activation gate drops to a value below that of bulk water density (Figures 2B and S1B), it is substantially higher than that in models of the open state of bacterial channels obtained experimentally, 23,24,29 leading us to hypothesize that the presence of π-helices correlates with an increased water density. Indeed, the experimentally resolved open-state model of Nav1.5 featured two π-helixes in DI-S6 and DIII-S6.…”
mentioning
confidence: 69%
“…3 More recent structures feature a short π-helix in either DI, DII, and DIII S6 or DI, DIII, DIV S6. 3,17−19 In our recent studies of bacterial Nav channels NavMs 23 and NavAb, 24 we found that introducing a short π-helical stretch in S6 of the channel resulted in the rotation of the S6 C-terminus and in increased pore hydration, allowing sodium ion permeation. This mechanism is consistent with that described in some TRP channels.…”
mentioning
confidence: 98%